2014
DOI: 10.3109/19396368.2014.968267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BHT inclusion on post-thaw attributes of human semen

Abstract: The aim of this study was to determine the effect of butylated hydroxytoluene (BHT) supplemented cryopreservation medium on sperm parameters during the freeze-thaw process. In addition, sperm lipid peroxidation, DNA damage, and the amount of reactive oxygen species (ROS) were determined. Semen samples were obtained from 75 donors. Fifteen semen samples were used for optimizing BHT concentration and incubation time and 60 samples were used for the final experiments. After the determination of basic parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
5
0
2
Order By: Relevance
“…During full‐text screening, no common antioxidants were identified in nineteen articles (Asadmobini, Bakhtiari, Khaleghi, Esmaeili, & Mostafaei, ; Brugnon et al, ; Fontoura et al, ; Isachenko et al, ; Kotdawala et al, ; Lu et al, ; Meamar et al, ; Naeini, Bafrani, & Nikzad, ; Najafi et al, ; Oehninger, Duru, Srisombut, & Morshedi, ; Parameswari et al, ; Pariz & Hallak, ; Saeednia et al, ; Sbracia, Grasso, Sayme, Stronk, & Huszar, ; Sobhani, Eftekhaari, Shahrzad, Natami, & Fallahi, ; Taylor, Roberts, Sanders, & Burton, ; Vickram et al, ; Werner et al, ), twelve articles lacked common sperm parameters (Banihani, Agarwal, Sharma, & Bayachou, ; Branco, Garcez, Pasqualotto, Erdtman, & Salvador, ; Donnelly, McClure, & Lewis, ; Esteves, Spaine, & Cedenho, ; Gadea et al, ; Garcez et al, ; Garcez, Branco, Lara, Pasqualotto, & Salvador, ; Jenkins, Aston, & Carrell, ; Li, Lin, Liu, Xiao, & Liu, ; Minaei et al, ; Nabi et al, ; Shabani Nashtaei et al, ) and one article lacked sufficient data (Karimfar et al, ). Finally, 23 articles (Aliabadi, Jahanshahi, Talaei‐Khozani, & Banaei, ; Askari, Check, Peymer, & Bollendorf, ; Azadi, Tavalaee, Deemeh, Arbabian, & Nasr‐Esfahani, ; Bateni et al, ; Deng et al, ; Duru, Morshedi, Schuffner, & Oehninger, ; Esteves, Sharma, Thomas, & Agarwal, ; Ghorbani et al, ; Kalthur et al, ; Keshtgar, Iravanpour, Gharesi‐Fard, & Kazerooni, ; Martinez‐Soto, Dioshourcade, Gutiérrez‐Adán, Landeras, & Gadea, ; Merino et al, ; Moubasher, Din, Ali, El‐sherif, & Gaber, ; Najafi et al, ; Nekoonam, Nashtaei, Naji, Zangi, & Amidi, ; Rossi, Mazzilli, Delfino, & Dondero, ; Taylor et al, ; Thomson et al, ; Varghese et al, ; Wang, Sikka, Veeraragavan, Bell, & Hellstr...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During full‐text screening, no common antioxidants were identified in nineteen articles (Asadmobini, Bakhtiari, Khaleghi, Esmaeili, & Mostafaei, ; Brugnon et al, ; Fontoura et al, ; Isachenko et al, ; Kotdawala et al, ; Lu et al, ; Meamar et al, ; Naeini, Bafrani, & Nikzad, ; Najafi et al, ; Oehninger, Duru, Srisombut, & Morshedi, ; Parameswari et al, ; Pariz & Hallak, ; Saeednia et al, ; Sbracia, Grasso, Sayme, Stronk, & Huszar, ; Sobhani, Eftekhaari, Shahrzad, Natami, & Fallahi, ; Taylor, Roberts, Sanders, & Burton, ; Vickram et al, ; Werner et al, ), twelve articles lacked common sperm parameters (Banihani, Agarwal, Sharma, & Bayachou, ; Branco, Garcez, Pasqualotto, Erdtman, & Salvador, ; Donnelly, McClure, & Lewis, ; Esteves, Spaine, & Cedenho, ; Gadea et al, ; Garcez et al, ; Garcez, Branco, Lara, Pasqualotto, & Salvador, ; Jenkins, Aston, & Carrell, ; Li, Lin, Liu, Xiao, & Liu, ; Minaei et al, ; Nabi et al, ; Shabani Nashtaei et al, ) and one article lacked sufficient data (Karimfar et al, ). Finally, 23 articles (Aliabadi, Jahanshahi, Talaei‐Khozani, & Banaei, ; Askari, Check, Peymer, & Bollendorf, ; Azadi, Tavalaee, Deemeh, Arbabian, & Nasr‐Esfahani, ; Bateni et al, ; Deng et al, ; Duru, Morshedi, Schuffner, & Oehninger, ; Esteves, Sharma, Thomas, & Agarwal, ; Ghorbani et al, ; Kalthur et al, ; Keshtgar, Iravanpour, Gharesi‐Fard, & Kazerooni, ; Martinez‐Soto, Dioshourcade, Gutiérrez‐Adán, Landeras, & Gadea, ; Merino et al, ; Moubasher, Din, Ali, El‐sherif, & Gaber, ; Najafi et al, ; Nekoonam, Nashtaei, Naji, Zangi, & Amidi, ; Rossi, Mazzilli, Delfino, & Dondero, ; Taylor et al, ; Thomson et al, ; Varghese et al, ; Wang, Sikka, Veeraragavan, Bell, & Hellstr...…”
Section: Resultsmentioning
confidence: 99%
“…BHT is another important scavenger of free radicals in freezing media responsible for reduction in SOD, glutathione peroxidase, and ROS production after cryopreservation and consequently protects sperm cells from DNA damage. Ghorbani et al indicated that damage to human sperm reduced in the BHT group compared to controls (25% and 49%, respectively) (Ghorbani et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…the samples were thawed and evaluated by computer analysis, as well as for membrane functionality and sperm morphology. Progressive motility in the 2.0 mM BHT group was significantly higher (P <0.05) than that of the 0 mM BHT group (27.6 ± 11.7% vs. 19.0 ± 9.5%, respectively). Regarding all other parameters evaluated, there was no difference between the groups tested.…”
mentioning
confidence: 77%
“…Em relação aos valores encontrados após a descongelação, foi possível perceber uma melhor qualidade da motilidade progressiva dos espermatozoides na concentração de 2,0 mM de BHT (27,6%), quando comparado ao grupo sem o antioxidante (19,0%). Esse resultado difere do encontrado por Ghorbani et al (19) em humanos, pois relataram que concentrações de BHT superiores a 0,5 mM resultaram em menor motilidade e viabilidade espermática provavelmente devido a um aumento de ânions superóxido e H2O2 nos espermatozoides. Khumran et al (26) relataram uma toxicidade causada pelo BHT, quando este é utilizado em concentrações maiores de 1 mM em sêmen de touros, levando a redução da motilidade e da viabilidade espermática.…”
Section: Discussionunclassified
See 1 more Smart Citation